1991
DOI: 10.1111/j.1558-5646.1991.tb05277.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation in a Fungal Pathogen: Response to Host Defensive Chemicals

Abstract: Abstract. -In response to infection by shoot infecting pathogens, Scots pine releases cortical resin into affected tissues. The resin contains a mixture ofmonoterpene compounds (a-pinene, tl-pinene, 3-carene, tl-myrcene, limonene and tl-phellandrene) that retard the growth ofa range of pathogens. The proportion of each monoterpene in the resin shows substantial variation among trees within a population. Thus pathogens on different trees encounter quite different monoterpene environments. To investigate the evo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1994
1994
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…For example, a purple pigment in the stem epidermis of wild soybean ( Glycine soja ) plants is correlated with resistance to the agromyzid fly Ophiomyia centrosematis (Chiang & Norris, 1984); the anthocyanidin malvadin was identified as the source of the purple colour in the stem epidermis, which was underlain by lignins and polyphenols which further contributed to insect resistance. It has been hypothesized that pathogens or herbivores may be subject to disruptive selection when they interact with chemically diverse host populations (but see Ennos & Swales, 1991). For example, selection for adaptation to the chemical phenotype of one host individual could result in reduced fitness on an alternative chemical phenotype, preventing the evolution of herbivores with high fitness on all plants (Dolinger et al ., 1973).…”
Section: Discussionmentioning
confidence: 99%
“…For example, a purple pigment in the stem epidermis of wild soybean ( Glycine soja ) plants is correlated with resistance to the agromyzid fly Ophiomyia centrosematis (Chiang & Norris, 1984); the anthocyanidin malvadin was identified as the source of the purple colour in the stem epidermis, which was underlain by lignins and polyphenols which further contributed to insect resistance. It has been hypothesized that pathogens or herbivores may be subject to disruptive selection when they interact with chemically diverse host populations (but see Ennos & Swales, 1991). For example, selection for adaptation to the chemical phenotype of one host individual could result in reduced fitness on an alternative chemical phenotype, preventing the evolution of herbivores with high fitness on all plants (Dolinger et al ., 1973).…”
Section: Discussionmentioning
confidence: 99%
“…However the trend, indicated by the exceptional family, of a genetic trade-off between pathogen level and plant size was not significant when the means of all families were correlated [genetic correlations in the sense of Via (1984)]. The evidence in the literature for fitness costs of plant resistance to pathogens seems to be relatively weak (Burdon 1987;De Nooij & Van Damme 1988;Parker 1990;Ennos & Swales 1991;Marquis & Alexander 1992).…”
Section: And Plant Performancementioning
confidence: 99%
“…Variation in correlation coefficients in resistance to DMI fungicides among populations was observed in a previous study [Peever and Milgroom, 1993]. These results have demonstrated that cross-resistance relationships can be quite variable among populations and among different combinations of SBI fungicides, even for fungicides with identical (Ennos and Swales, 1991). Confidence intervals not including 0 and 1 are significantly different from 0 and 1 at the 5% probability level.…”
Section: Phenotypic and Genetic Variation In Resistancementioning
confidence: 64%
“…Ninety five percent confidence intervals for the correlation coefficients were estimated using the method of Ennos and Swales [1991] as described in Peever and Milgroom [1993].…”
Section: Data Analysis Partitioning Variation In Resistance Phenotypementioning
confidence: 99%